The Indonesian government procurement system - Kartianingsih, Dwi Wahyuni (KDI School, 2001)
The procurement of goods and services for the government of the Republic of Indonesia is an important part of the efforts to achieve objectives and programs of development in accordance to national development planning. This paper examined the primary Indonesian Government Procurement regulation, titled "The Decree of The President of the Republic of Indonesia No. 18 Year 2000 Concerning Guidelines for The Implementation of The Procurement of Good and Services for Government Agencies". It is generally perceived that this procurement system is transparent and much in line with standards set by the international rules that are adopted in the WTO Government Procurement Agreement. However, despite the obligation under the most-favored-nation principle, the priority of the current Indonesian Government Procurement System is still to maximize the use of domestic products and services. From the multilateral perspectives, considering WTO as international rule, Indonesia has to emphasize fairness and non-discrimination in the process of procurement of goods and services for all participants, regardless local or foreign bidders. But it seems to contradict with what are .stipulated in the current regulation . The system explicitly states that one of the objectives for the government procurement policies is to "increase the use of domestic production, design and engineering with the aim of expanding domestic employment and national industries." Therefore, on the basis of the WTO rules, this regulation can be viewed as a protectionist rule to favor the domestic procedures. Therefore, Indonesia has to consider the WTO procurement system to fully incorporate the multilateral disciplines on government procurement in the future. However, the Indonesian government appears to take the position that government procurement systems should be an important instrument of national development, and therefore it should reserves its right to maintain this role.
Thesis(Master) --KDI School:Master of Public Policy,2001